Level of Regional Governments' Readiness to Deal with The Fourth Industrial Revolution Challenges: An E-Service Analysis - Sobari, Wawan; Priandani, Nurizal Dwi; Pohan, Ibnu Asqori (Journal of Local Government Issues, 2024)
The fourth industrial revolution (industry 4.0) has prompted major changes and challenges in all sectors, including governments. A recent theory explains that one of the challenges is changing needs for public services, requiring appropriate responses from the governments, both at national and regional levels. Departing from this situation, this study seeks to explore the readiness of regional governments to respond to the challenges. Through e-service assessment over applications developed by the Government of Malang Municipality, Malang Regency, and Batu Municipality (Greater Malang), document analysis, and focused group discussion, this study reveals several drawbacks of e-services, namely personnel’s readiness, users’ preparedness, flexibility, integration among applications, lack of socialization, weak support and commitment from leaders, low budget, and infrastructure constraints. These findings confirm previous studies on barriers to e-service delivery. This study also strengthens previous researches on the readiness of governments to meet the challenges of the revolution regarding the importance of administrative innovation initiatives and the role and commitment of leaders. Grounded on the logic beyond the implementation of e-services, this study offers an academic framework concerning the categories of regional governments’ preparedness to deal with the revolution’s challenges, namely the level of readiness for initiation, development, and sustainability.